English-in-Use in Cambridge test formats (Eurasian Journal of Philology Science and Education, 2016)
The paper considers historical background of test format developments by CELA. In this paper only the case of English language tests formats are considered. CELA has worked out its test structures and contents that coincide with the principle of usefulness. Validity, reliability, impact and practicality have enabled CELA tests to be further developed, and also facilitates CELA tests to be embedded both within and outside of the UK. Test tasks are worked out in the context of a communicative oriented approach. These factors allow CELA to create various tests that are able to test appropriate language levels for both academic and non-academic purposes.
Keywords: Cambridge English Language Assessment (CELA); test formats; English-in-Use.